Secular Trend in Portugal - Padez, Cristina (2007)
This study of secular trend in Portugal has shown that a positive increment in height occurred in Portuguese 18- year-old males between 1904 and 2000, and a secular trend in the age at menarche, towards an earliest age, also took place. Mean height increased 8.93 cm, from 1904 to 2000, when reached 172,13 cm. Besides that, in 2000, statistically significant differences (p ≤ 0.001) among the districts were found: males from Lisboa (172.79 cm) and Braga (172.67 cm), the most developed districts, are the tallest, and those from Madeira (170.67 cm), Castelo Branco, Leiria and Coimbra (171,31 cm) are the shortest. A decrease in age at menarche was observed: girls born in the decade 1880-90 had a mean age at menarche of 15 years and those born in 1970-1980 had a mean age at menarche of 12.03 years. The increase in mean stature and the decrease in mean menarcheal age represent a general improvement in the living conditions that occurred in Portugal after the 1970s. The Portuguese nutritional pattern, the health care system, the economy and even in housing conditions changed between 1960 and 1997